Ti Group Metallocene-Catalyzed Synthesis of 1-Hexene Dimers and Tetramers - Pavel V. Kovyazin; Almira Kh. Bikmeeva; Denis N. Islamov; Vasiliy M. Yanybin; Tatyana V. Tyumkina; Lyudmila V. Parfenova (Molecules, 2021)
1-Hexene transformations in the catalytic systems L2MCl2–XAlBui2 (L = Cp, M = Ti, Zr, Hf; L = Ind, rac-H4C2[THInd]2, M = Zr; X = H, Bu i) and [Cp2ZrH2]2-ClAlR2 activated by MMAO-12, B(C6F5)3, or (Ph3C)[B(C6F5)4] in chlorinated solvents (CH2Cl2, CHCl3, o-Cl2C6H4, ClCH2CH2Cl) were studied. The systems [Cp2ZrH2]2-MMAO-12, [Cp2ZrH2]2-ClAlBui2-MMAO-12, or Cp2ZrCl2-HAlBui2-MMAO-12 (B(C6F5)3) in CH2Cl2 showed the highest activity and selectivity towards the formation of vinylidene head-to-tail alkene dimers. The use of chloroform as a solvent provides further in situ dimer dimerization to give a tetramer yield of up to 89%. A study of the reaction of [Cp2ZrH2]2 or Cp2ZrCl2 with organoaluminum compounds and MMAO-12 by NMR spectroscopy confirmed the formation of Zr,Zr-hydride clusters as key intermediates of the alkene dimerization. The probable structure of the Zr,Zr-hydride clusters and ways of their generation in the catalytic systems were analyzed using a quantum chemical approach (DFT).